STRUCTURAL EQUATION MODELING-PARTIAL LEAST SQUARES (SEM-PLS) METHOD IN ANALYSIS OF THE EFFECT OF ANXIETY, FAMILY FUNCTION AND DEPRESSION ON THE QUALITY OF LIFE OF HEMODIALYSIS PATIENTS - Danang Kuswardono (Adisam Publisher, 2024)
This research aims to analyze the impact of worry/anxiety, family function, and depression on the quality of life of hemodialysis patients, using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data was collected from 58 hemodialysis patients at RSUD Dr. R. Soedjati Soemodiardjo Purwodadi Grobogan used a questionnaire that included an anxiety scale, family function scale, depression scale and quality of life scale. Data analysis was carried out using the SEM-PLS technique to test the relationship between variables. The results showed that anxiety had a significant influence on the patient's level of depression. This influence is a unidirectional influence, meaning that if the patient's anxiety increases, the level of depression also increases. Anxiety also has a significant influence on the quality of life of hemodialysis patients. This influence is a negative influence, meaning that increasing anxiety causes the patient's quality of life to decrease. Conversely, if anxiety decreases, the patient's quality of life increases.